Case Report: Multiple anterior chamber paracentesis or washout for a large hyphema following vitrectomy with silicone oil tamponade - Li, Jing; Peng, Jie; Luo, Qian; Zhang, Wanqiu; Yao, Yao; Chen, Shiyan; Zhou, Lin (Frontiers in Ophthalmology, 2025)
IntroductionTo report the management of a long-standing, large hyphema following vitrectomy with silicone oil tamponade using multiple anterior chamber paracentesis (ACP) or washout (ACW).Case presentationA 50-year-old woman presented with blurred vision attributed to polypoidal choroidal vasculopathy and vitreous hemorrhage. Vitrectomy with silicone oil tamponade and lens extraction were performed. A persistent large hyphema and elevated intraocular pressure were detected postoperatively. ACP and ACW were performed five and two times, respectively. The hyphema faded, and the elevated IOP decreased to the normal range within 2 months. The cornea was clear, and corneal blood staining was not observed.ConclusionsMultiple ACPs and ACWs are necessary and effective for the treatment of long-standing large hyphema.